2019
DOI: 10.1158/1078-0432.ccr-18-3040
|View full text |Cite
|
Sign up to set email alerts
|

Activated and Exhausted MAIT Cells Foster Disease Progression and Indicate Poor Outcome in Hepatocellular Carcinoma

Abstract: Purpose: Innate immunity is an indispensable arm of tumor immune surveillance, and the liver is an organ with a predominance of innate immunity, where mucosal-associated invariant T (MAIT) cells are enriched. However, little is known about the phenotype, functions, and immunomodulatory role of MAIT cells in hepatocellular carcinoma (HCC). Experimental Design: The distribution, phenotype, and function of MAIT cells in patients with HCC were evaluated by both flow cytometry (FCM) and in vitro bioassays. Transcri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
168
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(187 citation statements)
references
References 50 publications
(70 reference statements)
11
168
1
Order By: Relevance
“…Moreover, the abundance of this metacluster was reduced even further in cirrhotic compared to non-cirrhotic PBC patients. This finding is consistent with studies of other chronic liver diseases, including hepatitis B viral infection 26 and hepatocellular carcinoma 27 , which implicate exhaustion and loss of MAIT cells with worsening liver damage. Considering the apparent importance of these cells in PBC, our future efforts should include additional MAIT-specific markers such as the MAITinvariant T cell receptor (Vα7.2).…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, the abundance of this metacluster was reduced even further in cirrhotic compared to non-cirrhotic PBC patients. This finding is consistent with studies of other chronic liver diseases, including hepatitis B viral infection 26 and hepatocellular carcinoma 27 , which implicate exhaustion and loss of MAIT cells with worsening liver damage. Considering the apparent importance of these cells in PBC, our future efforts should include additional MAIT-specific markers such as the MAITinvariant T cell receptor (Vα7.2).…”
Section: Discussionsupporting
confidence: 91%
“…Recent studies have investigated the role of MAIT cells in cancer, and the observations reported are similar to those made in autoimmune and inflammatory diseases (TaBles 3,4). Circulating MAIT cell frequency is decreased in patients with colorectal cancer (CRC) [134][135][136] , hepatocellular carcinoma (HCC) 137 and lung cancer 136 . MAIT cells accumulate in tumour tissues from patients with colon adenocarcinomas 138 and CRC, particularly in those with advanced CRC [134][135][136] , and in hepatic metastatic lesions in patients with CRC 139 .…”
Section: Mait Cells In Human Cancersmentioning
confidence: 59%
“…As we observed in immunemediated diseases, this could reflect increased apoptosis of MAIT cells, possibly as a result of their chronic activation. Indeed, in patients with HCC, tumour-infiltrating MAIT cells had an exhausted phenotype, with high PD-1, CTLA4 and TIM3 expression, and produced less IFNγ and IL-17 than MAIT cells from healthy donors 137 . Similarly, MAIT cells from colonic adenocarcinomas produced less IFNγ than MAIT cells from healthy colons 138 , suggesting that tumour-infiltrating MAIT cells might be altered due to tumour microenvironmental factors.…”
Section: Mait Cells In Human Cancersmentioning
confidence: 98%
“…In hepatocellular carcinoma (HCC) patients, peripheral blood MAIT cells are numerically and functionally depleted [86]. Similar discoveries were made in terms of several chronic inflammatory conditions that are associated with an increased risk of malignant transformation in the liver, namely hepatitis C virus (HCV) infection [87], primary biliary cholangitis [88], and alcoholic and non-alcoholic fatty liver disease [89].…”
Section: Hepatic Malignanciesmentioning
confidence: 74%